THE INFLUENCE OF SERVICE QUALITY AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY IN DANA APPLICATION - Afifah Dian Septiantika; Indira Rachmawati (Jurnal Ekonomi, 2023)
The problem behind this research is to identify the causes of the decline in customer loyalty that occurs due to decreased service quality and customer satisfaction provided by the company for DANA application users. This study aims to identify the effect of service quality and customer satisfaction on customer loyalty in the DANA application. The method used in this study is a quantitative method. The population in this study is Indonesian people who are users of the DANA application. The sampling technique used in this study is a non-probability sampling technique with a total of 400 respondents. Data analysis techniques were carried out in this study using the Structural Equation Modeling (SEM) method with AMOS software. The results of this study show that service quality has a significant and positive effect on DANA customer satisfaction, service quality has a significant and positive effect on DANA customer loyalty, service quality and customer satisfaction has a significant and positive effect on DANA customer loyalty. Based on the results of hypothesis testing, service quality has the greatest influence in this study so that it is expected that companies can maintain good service quality to maintain relationships with customers.